Chelonastichus Ranjith & Quicke, gen. nov. (Hymenoptera, Eulophidae, Tetrastichinae) from Thailand: the first eulophid with a metasomal carapace - Avunjikkattu Parambil Ranjith; Donald L. J. Quicke; Kittipum Chansri; Buntika A. Butcher (Journal of Hymenoptera Research)
Chelonastichus Ranjith & Quicke, gen. nov., is described based on a new species, C. hanssoni Ranjith & Quicke, sp. nov., from Thailand. Whereas most Eulophidae exhibit a delicate, collapsible body, the new genus, is the first known case within the family that possesses a coarsely-sculptured metasomal carapace formed by Gt5, with Gt2–4 short. The possible affinities of the new genus are discussed and it is tentatively placed in the Tetrastichinae.